2015
DOI: 10.1038/emm.2015.30
|View full text |Cite
|
Sign up to set email alerts
|

NADPH oxidase activation contributes to native low-density lipoprotein-induced proliferation of human aortic smooth muscle cells

Abstract: Elevated plasma concentration of native low-density lipoprotein (nLDL) is associated with vascular smooth muscle cell (VSMC) activation and cardiovascular disease. We investigated the mechanisms of superoxide generation and its contribution to pathophysiological cell proliferation in response to nLDL stimulation. Lucigenin-induced chemiluminescence was used to measure nLDL-induced superoxide production in human aortic smooth muscle cells (hAoSMCs). Superoxide production was increased by nicotinamide adenine di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
0
8
0
1
Order By: Relevance
“…13 Further, gene silencing techniques reveal cellular events involved in neointima formation to be driven by Nox1 activation in cell lines of vascular smooth muscle cells, namely, phenotypic modulation and proliferation in response to cyclic stretch 14 and low density lipoprotein. 15 This putative role of Nox1 in diabetes-induced atherosclerosis holds true in the intact animal, as demonstrated by the seminal paper by Gray et al . In this study, genetic deletion of Nox1, but not Nox4, abolished atherosclerotic lesion development in aortae of ApoE −/− mice made diabetic by daily injections of streptozotocin.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…13 Further, gene silencing techniques reveal cellular events involved in neointima formation to be driven by Nox1 activation in cell lines of vascular smooth muscle cells, namely, phenotypic modulation and proliferation in response to cyclic stretch 14 and low density lipoprotein. 15 This putative role of Nox1 in diabetes-induced atherosclerosis holds true in the intact animal, as demonstrated by the seminal paper by Gray et al . In this study, genetic deletion of Nox1, but not Nox4, abolished atherosclerotic lesion development in aortae of ApoE −/− mice made diabetic by daily injections of streptozotocin.…”
Section: Discussionmentioning
confidence: 87%
“…12 Nox1, expressed in endothelial cells and vascular smooth muscle cells 11 , may be a key driver of oxidative stress within an aberrant metabolic state given that its activity in vitro is induced in the presence of high glucose or saturated fatty acids. 1215 Indeed, our laboratory previously demonstrated that restoring glycemic control via deletion of PTP1B or myostatin, improved microvascular function and attenuated Nox1 expression. 16 These findings suggest that the metabolic milieu of obesity is transduced to the vasculature through Nox1.…”
Section: Introductionmentioning
confidence: 99%
“…We previously demonstrated that nLDL induced VSMC proliferation through activation of NADPH oxidase and that phosphorylation of both PKCβ and ERK1/2 was responsible for p47phox translocation to the membrane. 3 Therefore, we tested whether limonin prevented nLDL-induced activation of PKCβII and ERK1/2. Interestingly, limonin abolished PKCβII phosphorylation at 10 min in nLDL-stimulated VSMCs ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The chemiluminescence intensity in all experiments was measured for 5 min, and the values are presented as relative lucigenin units/min. 3 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation